APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) PADA DISTRIBUSI SELEDRI (Apium graveolens L.) DARI PETANI DI KECAMATAN BATURITI KE PENGECER. - Wintagata, Kadek Adi; Hartiati, Amna; Admadi, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The purpose of this research is 1). to determine the number of distribution paths celery (Apiumgraveolens L.), the type of distribution lines 2). postharvest handling of celery, and the impact of postharvest losses and the value of the damage of farmers to retailers Baturiti district. The method used in this research is survey method with the application of the Commodity Systems Assessment Method in the form of questionnaires distributed to farmers, collectors, wholesalers, suppliers and retailers of celery. There are four lines of celery distribution, there are, the first (I) is farmers ? retailers, the second (II) is farmers ? collectors ? retailers, the third (III ) is farmers ? collectors ? wholesalers ? retailers, and the last (IV) is farmers ? collectors ? wholesalers ? suppliers ? retailers. Post-harvest handling at the farm level include harvesting, sorting and cleaning, packaging and transportation. Post-harvest handling at the level of collectors, and wholesalers include weighing, sorting, and transporting, postharvest handling at the retail level covering inspection, packaging, and display, postharvest handling at the level of suppliers includes weighing, sorting, packaging and transportation, postharvest handling level includes supermarkets weighing, inspection, and display. Impact on celery postharvest losses at the farm level, namely the harvest reached 14,53% (significant), at the level of the collectors in the transport process is reached 0,44% (insignificant), at the level of big traders when transporting reached 0% (insignificant), at the retails level in sorting reached  0% (insignificant), at the sorting supplier level reached 1,55% (significant). Keyword: Distribution line, CSAM, postharvest, celery.